Pharmacist-strengthen Adherence to Antiretroviral Therapy and the Contributing Factors among HIV-infected Paediatric Patients in Nigeria - Bello, Shakirat Tyabo (Bangladesh Journal of Medicine, 2017)
Introduction: Children adherence to Highly Active Antiretroviral Therapy (HAART) not only creates a problem for the treated children, but also for their caregivers and healthcare providers. The objective of this study was to determine adherence level and evaluate factors associated with better drug adherence among HIV-infected children in Nigeria. Methods: Adherence to HAART was determined prospectively among HIV-infected children attending HAART Clinic in the University of Ilorin Teaching Hospital, Ilorin, Nigeria. Adherence level was measured using self-reported method and patients medical folders. Logistic regression analysis was used to assess factors associated with better drug adherence among the children. Results: In the eighty children studied, mean age at baseline was 2.16±0.74 years and 60% were males. Baseline adherence level was 74.0% which improved to 98.0% over the course of 8-months follow-up intervention by the pharmacist (p<0.043). Forgetfulness of caregivers to administer antiretroviral medication at the right time to the children was the highest reason for non- adherence. Factors associated with better drug adherence were duration on HAART (OR 1.201; 0.253-1.144, p< 0.003), age (OR 0.540; 0.162-1.006, p < 0.001), type of regimen (OR 0.222; 0.134-1.356, p< 0.046) and heavier weights (OR 1.559; 0.403-1.826, p < 0.023). Conclusions: Following pharmacists intervention coupled with other factors, adherence to HAART was strengthened with significant improvement in the children medication-taking behaviour. Bangladesh J Medicine Jan 2017; 28(1) : 5-12